Impact of Multileaf Collimator Width and Normal Tissue Objective on Radiation Dose Distribution in Stereotactic Radiosurgery Using HyperArc for Single Brain Lesions - Se An Oh; Jae Won Park; Ji Woon Yea; Jaehyeon Park; Yoon Young Jo (Current Oncology)
This study retrospectively investigated the impact of stereotactic radiosurgery (SRS) normal tissue objective (NTO) and multileaf collimator (MLC) width on radiation dose distribution in patients with brain metastasis treated using HyperArc. In total, 21 patients who underwent SRS using the HyperArc of the TrueBeam linear accelerator from November 2022 to June 2024 were included. All patients received radiotherapy with HASH planned with SRS NTO and HD MLC. HyperArc(HAAH) combined with the auto NTO and HD MLC and HyperArc(HAAM) with auto NTO and millennium MLC were generated and compared. Monitor units (MU), conformity index (CI), radical dose homogeneity index (rDHI), moderate DHI (mDHI), and gradient index (GI) were evaluated as target factors, and V2(Gy), V10(Gy), V12(Gy), V18(Gy), V10(cc), and V12(cc) were evaluated as normal brain factors. Dosimetric comparisons were performed between HASH, HAAH, and HAAM and between target and normal brain tissues. Between HASH and HAAH, average MU was 7206 and 5798, respectively; the difference was significant (p < 0.001). The MU of HAAM was 5835. Among HASH, HAAH, and HAAM, CI and mDHI were not significantly different, but there were significant differences in rDHI, GI, and normal brain tissues. When treating a single lesion using HyperArc, SRS NTO influences MU and GI, and the MLC width influences rDHI and GI. In HyperArc for single metastatic brain lesions, SRS NTO and MLC width have a significant effect on the radiation dose delivered to the target and normal brain tissues.